EXPERIMENTAL DETERMINATION OF CONVECTIVE HEAT TRANSFER COEFFICIENTS IN THERMAL BUOYACY VENTILATION SYSTEM - D. V. Abramkina; A. A. Abramyan; E. R. Shevchenko-Enns (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives. The main goal of the article is to present the developed method for the experimental determination of convective heat transfer coefficients, suitable for studying the internal convection of models of complex configuration. Method. The study of free convection under the conditions of an internal problem was carried out by determining the conditional thickness of the boundary layer by a graphic method. The first was the selection of the calculated sections and planes for the experimental installation. The selection is carried out in such a way that the calculated planes are perpendicular to the heated walls of the channel in question. Installation of an experimental model is possible only in a room with low internal air mobility, as well as a stable temperature. In this room there should not be heating and heating devices that can create strong convective currents near the channel of the experimental installation. Result. The article presents the results of an experimental study to determine the temperature distribution of the air flow and average convective heat transfer coefficients over the height of the ventilation channel. A decrease in convective heat transfer coefficients at an altitude of 0.5 to 1 meter occurs less noticeably than at an altitude of 1 to 2 meters, which is associated with the restoration of flow after a vent removal. At the stabilization section, there is first a gradual decrease, and then an increase in axial velocity, which is caused by the merging of multidirectional air flows in this area. Conclusion. It was revealed that in the case of modeling free convection under the conditions of an internal problem in the presence of heat-removing boundaries  within the limits of the calculated temperature difference, taking into account the flow turbulization has practically no effect on the final results.